A serological survey of anthrax in domestic dogs in Zimbabwe: a potential tool for anthrax surveillance. Issue 12 (14th June 2018) - Mukarati, N. L.; Ndumnego, O.; van Heerden, H.; Ndhlovu, D. N.; Matope, G.; Caron, A.; de Garine-Wichatitsky, M.; Pfukenyi, D. M.
Abstract: Anthrax is an important disease caused by the bacterium Bacillus anthracis affecting both domestic and wild animals at the wildlife/livestock interface, defined here as a physical space in which wild and domestic species overlap in range and potentially interact. In endemic regions, sporadic anthrax outbreaks occur, causing significant deaths of both wildlife and livestock and sporadically, humans. However, it may also occur as isolated outbreaks with a few animals affected. Such isolated anthrax outbreaks maybe missed. High seroprevalence among carnivores suggests either regular non-fatal exposure to the pathogen circulating in a given environment, or contact with missed cases through consumption of anthrax carcases. To investigate the relevance of this potential indicator, a cross-sectional study was conducted to determine anthrax seroprevalence in domestic dogs ( Canis lupus familiaris) from selected interface and non-interface areas of Zimbabwe with known history of anthrax outbreaks. Based on past anthrax outbreaks in the respective areas, the sites were further classified as high or low risk areas for anthrax outbreaks. Sera were collected from domestic dogs ( n = 186) and tested for antibodies against B. anthracis protective antigens (PA) using an ELISA test. The overall seroprevalence was 51.6% (96/186; 95% CI 44.2–59.0). Sites from the non-interface areas recorded a significantly ( P < 0.001) higher (72.1%) anthrax seroprevalence compared with those from the wildlife –livestock interface (41.5%). The results demonstrated a strong association ( χ 2 = 14.3; OR = 3.2, 1.6 < OR < 6.2, P < 0.001) between anthrax seropositivity and interface type. Low-risk sites (42.5%) had a significantly ( P = 0.044) lower seroprevalence compared with high-risk sites (58.5%) but still demonstrated high seroprevalence for areas where anthrax was last reported more than 20 years back. Dogs from Tsholotsho South were more than 90-times (OR = 96.5, 13.5 < OR < 690.8) more likely to be seropositive compared with those from Hwange. The study demonstrated the potential to use domestic dogs as indicators of anthrax in the study areas to survey anthrax circulation in supposed low-risk areas and calls for a redefinition of both low and high risk areas for anthrax in Zimbabwe based on an improved surveillance.